Four 3, 5-diamino-1, 2, 4-triazole-based cobalt(II/III) complexes incorporating with 5-substituted isophthalate coligands: Synthesis, structure and magnetism. (24th November 2015) - Zhao, Hong; Li, Hong-Xue; Liu, Zhong-Yi; Yang, En-Cui; Zhao, Xiao-Jun
Graphical abstract: Four coordination polymers with binuclear subunit, helical chain, distorted triangular and (4, 4) topological layer were generated by varying the substituent of isophthalate in the ternary Co II -3, 5-diamino-1, 2, 4-triazolate-isophthalate system. Three of them exhibit metamagnetic transition and typically antiferromagnetic interactions. Abstract: Four 3, 5-diamino-1, 2, 4-triazole (Hdatrz)-based cobalt(II/III) coordination polymers, [Co2 (Hdatrz)(NH2 -ip)2 ]·0.5H2 O n (1 ), [Co(CH3 OH)(Hdatrz)(CH3 -ip)] n (2 ), [Co2 (datrz)2 (CH3 -ip)]·2.5H2 O n (3 ) and [Co(datrz)(NO2 -ip)]·H2 O n (4 ) (NH2 -ip 2− = 5-aminoisophthalate, CH3 -ip 2− = 5-methylisophthalate and NO2 -ip 2− = 5-nitroisophthalate), were hydro-/solvothermally synthesized by changing the substituents attached on the isophthalate coligand, which were structurally and magnetically characterized. Complex1 is a corrugated layer with dimeric Co2 (μ-N1, N2-Hdatrz) 4+ subunits extended by three-connected NH2 -ip 2− connectors. Constructed from the same mixed ligands, both2 and3 exhibit robust three-dimensional (3D) frameworks consisting of helical Co(μ-N1, N4-Hdatrz) 2+ chain and corner-sharing triangular Co2 (μ3 -N1, N2, N4-datrz)2 2+ layer, respectively. By contrast, two bis-monodentate NO2 -ip 2− and two μ-N1, N4-datrz − anions connect tetrahedral Co(III) sites into a (4, 4) grid-like layer of4 . Thus, the substituent of the isophthalate coligand is observed to virtually influence the overall structures of the resulting complexes by changing the binding modes of the coligand and coordination polyhedra. Additionally, complex1 exhibits a metamagnetic transition from antiferromagnetic ordering to weak ferromagnetic state. Instead, typically antiferromagnetic interactions are respectively mediated by the cyclic triazolate ligand along the helical chain of2 and in the distorted triangular layer of3 .